Mir-155 knockout protects against ischemia/reperfusion-induced brain injury and hemorrhagic transformation. Issue 3 (5th February 2020) - Suofu, Yalikun; Wang, Xiaomin; He, Yanqing; Li, Fang; Zhang, Yu; Carlisle, Diane L.; Friedlander, Robert M.
Abstract : MiR-155 negatively regulates translation of mRNA targets to proteins involved in processes that modulate ischemic brain injury including neuroinflammation, blood-brain barrier (BBB) permeability, and apoptosis. However, reports of the effect of cerebral miR-155 expression changes after ischemic brain injury are equivocal and miR-155 modulates molecular pathways with opposing effects on these processes. The role of miR-155 in postischemic cerebral hemorrhagic transformation remains unknown. To understand the net effect of complete inactivation of miR-155, miR-155 knockout mice were studied in a cerebral ischemia/reperfusion (I/R) model of infarction and hemorrhagic transformation as compared with those of wild type mice. Wild type and miR-155 knockout mice underwent one hour of middle cerebral artery occlusion (MCAO) followed by up to 71 hours of reperfusion. The effects of miR-155 knockout on cerebral infarct size, incidence and extent of hemorrhagic transformation, and neurological outcome were determined. We found that miR-155 was significantly upregulated after cerebral I/R in wild type mice, and miR-155 knockout mice had comparably smaller cerebral infarct size and improved neurological deficits. Similarly, wild type mice had significant hemorrhagic burden after cerebral I/R, the incidence and volume of which was reduced in miR-155 knockout mice. Although miR-155 can have opposite effects on cerebral I/R-injury-related processes, the net effect of miR-155 knockout is neuroprotective. Thus, the increase in miR-155 expression observed after cerebral I/R may be considered deleterious and inhibition of this expression and its effects a potential therapeutic target.